A factory fracturing model of multi-well cluster in Sulige gas field, NW China - Mingfang HE; Xu MA; Yanmin ZHANG; Xuan'ang LAI; Yuanxiang XIAO; Ruifen HAO (Petroleum Exploration and Development, 2014)
Sulige gas field is a typical low-permeability reservoir in China. According to desert landform features along with the regional hydrologic feature and the existing fracturing technology and operational conditions, a factory-like fracturing method suitable for Sulige gas field is established to improve techniques and production organization. This method includes five key parts: (1) centralized water supply mode (water source well supply+artificial lake storage); (2) highly efficient fracturing process (two mature multi-stage fracturing technologies, sliding sleeve fracturing for vertical wells and open-hole packer fracturing for horizontal wells); (3) pipeline operation mode with seven procedures, including well drift and flushing perforation etc; (4) high efficiency operation equipment; (5) recovery of fracturing flow-back fluid. This method shortens the preparation and operation period of fracturing treatment and also relieves the pressure on environment. Pilot tests were carried out in 11 well groups in total. Sixty-seven stages of fracturing in 14 wells were successfully completed within 42 days, representing a reduction of fracturing operation cycle of more than 50%, and an encouraging improvement in efficiency. Key words: Sulige gas field, factory fracturing, big well group, water supply, fracturing process, pipeline operation, fluid recovery, high efficiency, environment friendly